Identifying the winter grounds of the recently described Barbary Reed Warbler (Acrocephalus baeticatus ambiguus). (27th July 2022) - Jiguet, Frédéric; Dufour, Paul; Kardynal, Kevin J.; Hobson, Keith A.; Copete, José Luis; Arroyo, Jose Luis; Lee, Raymond W.; Rguibi‐Idrissi, Hamid; Procházka, Petr
Abstract : The Iberian and North African populations of reed warblers have been described recently as a separate taxon, ambiguus, forming a sister clade to the Sahelian subspecies minor of African Reed Warbler Acrocephalus baeticatus . Although the breeding range of ambiguus has been identified, the migration strategy of its populations remained unknown. We deployed geolocators and sampled the innermost primary from breeding adults in Spain for stable hydrogen ( δ 2 H) analyses and also analysed stable carbon ( δ 13 C) and nitrogen ( δ 15 N) isotopes in feathers collected in two reed warbler taxa ( Acrocephalus scirpaceus and Acrocephalus baeticatus ambiguus ) in Morocco, to identify the moulting and wintering sites of these populations. Ring recoveries, geolocator tracks and probabilistic assignments to origin from δ 2 H values indicate that Spanish ambiguus are likely to moult south of the Sahara and winter in West Africa, probably from Mauretania to southern Mali and Ivory Coast. Moroccan ambiguus, however, undergo post‐breeding moult north of the Sahara, and possibly then migrate to West Africa. With other populations of ambiguus breeding from Algeria to Libya and probably wintering further east in the Sahelian belt, the Barbary Reed Warbler can therefore be considered a trans‐Saharan migrant, with a post‐breeding moult strategy that varies between populations, and probably structured according to breeding latitude.